Bone morphology is regulated modularly by global and regional genetic programs - Eyal, Shai (Development, 2019)
Bone protrusions provide stable anchoring sites for ligaments and tendons and define the unique morphology of each long bone. Despite their importance, the mechanism by which superstructures are patterned is unknown. Here, we identify components of the genetic program that control the patterning of Sox9(+)/Scx(+) superstructure progenitors in mouse and show that this program includes both global and regional regulatory modules. Using light-sheet fluorescence microscopy combined with genetic lineage labeling, we mapped the broad contribution of the Sox9(+)/Scx(+) progenitors to the formation of bone superstructures. Then, by combining literature-based evidence, comparative transcriptomic analysis and genetic mouse models, we identified Gli3 as a global regulator of superstructure patterning, whereas Pbx1, Pbx2, Hoxa11 and Hoxd11 act as proximal and distal regulators, respectively. Moreover, by demonstrating a dose-dependent pattern regulation in Gli3 and Pbx1 compound mutations, we show that the global and regional regulatory modules work in a coordinated manner. Collectively, our results provide strong evidence for genetic regulation of superstructure patterning, which further supports the notion that long bone development is a modular process. This article has an associated ‘The people behind the papers’ interview.